COMMUNICATING ENVIRONMENTAL RESPONSIBILITY: CSR BENIH BAIK AND THE CONSTRUCTION OF GARUDA INDONESIA’S GREEN AIRLINE IMAGE - Dela Anjelawati; Dinda Amaris (Universitas Nasional, 2025)
The intensification of global environmental crises has compelled the aviation sector to adopt Corporate Social Responsibility (CSR) not merely as a philanthropic obligation but as a vital strategic communication tool for reputation management. This study critically analyzes the